Metro music celebrating a century of the Trinity River groove - Fowler, Gene 1950- (TCU Press, 2021)
"Metro Music explores the musical history of Dallas, Fort Worth, and the surrounding area from the nineteenth century to the 1960s and the continuing echoes of that transformative decade. With nearly five hundred images, many previously unpublished, the book moves through genres and eras that include old-time fiddlers and string bands, singing cowboys, the blues, western swing, gospel, country-western, jazz, ragtime, big bands, Tejano and Tex-Mex, rhythm and blues, rockabilly, and rock 'n' roll"
Includes index
Keywords: Geschichte 1880-1970; Musik; Fort Worth, Tex.; Dallas, Tex. -- Region; Popular music / Texas / Dallas / History and criticism; Popular music / Texas / Fort Worth / History and criticism; Musicians / Texas / Pictorial works; Dallas (Tex.) / Social life and customs / Pictorial works; Fort Worth (Tex.) / Social life and customs / Pictorial works; Badu, Erykah; Manners and customs; Musicians; Popular music; Texas; Texas / Dallas; Texas / Fort Worth; Criticism, interpretation, etc; Pictorial works